The Development Of Encapsulation-Dehydration And Vitrification Protocols For Protocorm-Like Bodies (PLBs) Of Dendrobium Sonia-28 - Poobathy, Ranjetta (2012)
The vitrification and encapsulation-dehydration methods of cryopreservation were applied on protocorm-like bodies (PLBs) of the orchid hybrid Dendrobium sonia-28, with survival assessments conducted through growth observations, visualand spectrophotometric 2,3,5-triphenyltetrazolium chloride (TTC) assays. The best survival (16.0% regeneration) for vitrification was obtained when 3-4mm PLBs were precultured in semi-solid half-strength MS medium supplemented with 0.4M sucrose, loaded in a loading solution for 20 minutes, dehydrated for 50 minutes at 0°C in plant vitrification solution 2 (PVS2), cryopreserved in liquid nitrogen (LN) for 24 hours, thawed in a 40±2°C water bath for 90 seconds, unloaded in 1.2M sucrose for 20 minutes, and regenerated in semi-solid half-strength MS medium containing 2g.L-1 charcoal, with all media supplemented with 0.6mM ascorbic acid.